Pengaruh Capital Intensity, Risiko Perusahaan, Kompensasi Rugi Fiskal Terhadap Penghindaran Pajak - Muhammad Ichsan Kamil; Masripah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to determine the effect of capital intensity, company risk and fiscal loss compensation on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2020. This study is a quantitative study with secondary data consisting of 75 samples of companies collected using purposive sampling method. data analysis technique in this study uses a regression model selection test, classical assumption test of panel data regression and hypothesis testing and is processed using software STATA version 16. Bases on the results, it is known that simultaneously capital intensity, corporate risk and fiscal loss compensation are significant to tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2017 to 2020. The partial test results of this study indicate that (1) capital intensity has no significant effect on tax avoidance, (2) company risk has a significant positive effect on tax avoidance, (3) fiscal loss compensation has no significant effect on tax avoidance. The ability of capital intensity, corporate risk, fiscal loss compensation in explaining avoidance is 9,58% and the remaining 90,42% influenced by other factors.